Intensification of Thermal Performance of a Heat Exchanger Tube with Knitted Wire Coil Turbulators Installed - K. Wongcharee; Thiri Shoon Wai; Naoki Maruyama; Masafumi Hirota; V. Chuwattanakul; Pitak Promthaisong; Smith Eiamsa–ard (Eng—Advances in Engineering, 2025)
This study reports on heat transfer augmentation by knitted wire coil turbulators in a fully developed turbulent regime. Four knitted wire coil turbulators with different wire loop number densities (N = 6, 8, 10, and 12 loops per pitch, with 1.0 pitch = 6.8 mm) were tested. Each was made by winding a 0.7 mm copper wire around a 1.0 mm core rod. Experiments were conducted under a constant 600 W/m2 wall heat flux. The flow behaviors observed through a dye injection technique revealed that the wire coil induced secondary flows and developed shear layers, contributing to enhanced heat transfer. Heat transfer improved with increasing wire loop number density. Application of knitted wire coil turbulators increased the Nusselt number (Nu) by 86, 95.4, 103.2, and 109.3% for N = 6, 8, 10, and 12, respectively. This corresponded to increased friction factors (f) by 1.77, 1.97, 2.15, and 2.31 times, respectively. The tube with coils having N = 12 yielded the highest thermal performance index (TPI), 1.4, at a Reynolds number of 5000. The empirical correlations for Nu, f, and TPI showed deviations within ±2.1, ±0.68, and ±2.28%, respectively.
Keywords: Heat Transfer Mechanisms; Heat Transfer and Optimization; Nanofluid Flow and Heat Transfer